Amplifying women’s voice and agency in climate-related governance and policies - Awinoh, Martha; Ngugi, Elphas (CGIAR, 2024)
Jordan Kyle, lead of HER+ initiative VOICE work package highlights new tools to measure women’s voice and agency in agrifood policymaking and agrifood value chains advanced and communicated evidence around raising women’s influence in public and private sector climate-relevant governance and decision-making.